Pemberantasan Penjualan Handphone Black Market (Studi Penelitian di Pematang Siantar) - Christian maichel; Zulfan Z; Muhammad Hatta (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
The purpose of this study is to identify and discuss law enforcement against the sale of blackmarket mobile phones in Pematang Siantar and the role of the police and the Department of Industry and Trade in eradicating the sale of blackmarket mobile phones in Pematang Siantar. This study uses the empirical juridical method, which is a phenomenon that occurs using a theoretical basis in order to explain conformity with the facts on the ground. The data in this study were obtained from the results of interviews with informants and several expert sources in this study. Furthermore, the data is validated according to what is obtained in the field from the results of interviews.